The Relationship Between Body Mass Index (BMI) and Blood Pressure in Hypertensive Patients at Ciptodadi Community Health Center, Musi Rawas Regency, and Its Review from an Islamic Perspective - Keisa Yude Prameswari; Diniwati Mukhtar; Muhammad Arsyad (Jurnal Indonesia Sosial Sains, 2025)
This study examines the relationship between Body Mass Index (BMI) and blood pressure (hypertension) in the Ciptodadi Community Health Center, Musi Rawas Regency. Hypertension, a non-communicable disease, is influenced by factors like BMI, with higher BMI contributing to increased blood pressure. An observational analytical study with a cross-control approach involved 60 respondents, 30 with hypertension and 30 without. Blood pressure and BMI were measured, and data were analyzed using the Chi-Square test. The results indicated a significant relationship between BMI and blood pressure, with 40% of respondents with a BMI ≥23 kg/m² having hypertension, compared to 16.7% without hypertension. The Chi-Square test yielded a p-value of 0.00, with an odds ratio (OR) of 8.000, suggesting a significant association between BMI and hypertension. The study concludes that individuals with excess BMI are at a higher risk of developing hypertension. From an Islamic perspective, maintaining BMI and blood pressure aligns with the obligation of hifz an-nafs (preserving the soul).